2017
DOI: 10.11604/pamj.2017.26.36.8746
|View full text |Cite
|
Sign up to set email alerts
|

Role of H-FABP values in determining the etiologic factors of the cardiac injuries

Abstract: IntroductionCardiac injury resulting from blunt thoracic trauma is a frequent clinical occurrence which is difficult to diagnose. Our purpose in this study was to research whether H-FABP, which is a new marker for the diagnosis of cardiac injury, can be used in this patient group.Methods50 patients with blunt thoracic injury who were admitted to our emergency service within a period of 8 months and 50 cases as controls were included in our study.ResultsOf the 50 patients with blunt thoracic injury in our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In most cases, restoration of sinus rhythm was spontaneous or under medical treatment, within one hour to a week after CABG. Thus, ischemic lesion during open heart surgery should represent a therapeutic objective in order to reduce the occurrence of POAF [14]. Recent studies have shown that H-FABP can be used especially in early diagnosis of acute coronary syndrome, heart failure, liver and kidney lesions, pulmonar y thromboembolism and some kind of intoxications.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, restoration of sinus rhythm was spontaneous or under medical treatment, within one hour to a week after CABG. Thus, ischemic lesion during open heart surgery should represent a therapeutic objective in order to reduce the occurrence of POAF [14]. Recent studies have shown that H-FABP can be used especially in early diagnosis of acute coronary syndrome, heart failure, liver and kidney lesions, pulmonar y thromboembolism and some kind of intoxications.…”
Section: Resultsmentioning
confidence: 99%
“…In assessment of the H-FABP in relation to BCI, no significance was found between cardiac injury due to blunt thoracic trauma and H-FABP ( P > 0.05); therefore, it is recommended to conduct wide-scale prospective studies for its use in this context. [28]…”
Section: Diagnosticsmentioning
confidence: 99%
“…It is also responsible for the synthesis of membranes and mediators, it influences gene expression, and it protects cells during ischemia by inactivating radicals. It is excreted renally and has a half-life of 20 min [ 5 ].…”
Section: Introductionmentioning
confidence: 99%